Decreased prolyl hydroxylase 3 mRNA expression in oncocytomas compared with clear cell renal cell carcinoma. Issue 4 (December 2020) - Kampantais, Spyridon; Kounatidis, Ilias; Kotoula, Vasiliki; Vakalopoulos, Ioannis; Gkagkalidis, Konstantinos; Dimitriadis, Georgios
Introduction: Hypoxia inducible factors (HIF) and prolyl hydroxylase domain (PHD) enzymes play a central role in tumor progression in clear cell renal cell carcinoma (ccRCC). However, there are currently no data regarding the behavior of this pathway (HIF/PHD) in a large number of benign renal tumors, the oncocytomas. The aim of the present study was to compare the expression levels of these factors between ccRCC and oncocytoma tumors. Material and methods: A total of 56 fresh frozen specimens from patients with ccRCC and 14 oncocytoma specimens were analyzed via reverse transcription-quantitative polymerase chain reaction in order to assess the expression levels of HIF-1α, HIF-2α, PHD1, PHD2, and PHD3. The analysis involved both fresh frozen tumor samples as well as adjacent normal kidney tissues. Results: In ccRCC, HIF-1α and HIF-2α levels were upregulated in 65.5% and 71.4% of cases, respectively. PHD3 was downregulated only in 15.4% of the ccRCC cases, in contrast with oncocytoma cases, which exhibited low expression levels in the majority. The upregulation of PHD3 messenger RNA (mRNA) levels in ccRCC when compared with oncocytoma was statistically significant ( P <0.001). No other comparisons (HIF-1α, HIF-2α, PHD1, and PHD2) were significantly different. HIF-2α and PHD3 mRNA expression levels were negatively correlated with Fuhrman Grade ( P =0.029 and P =0.026, respectively) in ccRCC. Conclusion: To the best of our knowledge, this is the first time that the HIF/PHD pathway was compared between ccRCC and a common benign tumor, identifying the upregulation of PHD3 as the possible underlying factor guiding the difference in the behavior of ccRCC.